Phenotype of NK-Like CD8(+) T Cells with Innate Features in Humans and Their Relevance in Cancer Diseases - Barbarin, Alice; Cayssials, Emilie; Jacomet, Florence; Nunez, Nicolas Gonzalo; Basbous, Sara; Lefèvre, Lucie; Abdallah, Myriam; Piccirilli, Nathalie; Morin, Benjamin; Lavoue, Vincent; Catros, Véronique; Piaggio, Eliane; et al. (Frontiers in Immunology, 2017)
Unconventional T cells are defined by their capacity to respond to signals other than the well-known complex of peptides and major histocompatibility complex (MHC) proteins. Among the burgeoning family of unconventional T cells, innate-like CD8(+) T cells in the mouse were discovered in the early 2000s. This subset of CD8(+) T bears a memory phenotype without having encountered a foreign antigen and can respond to innate-like IL-12+IL-18 stimulation. Although the concept of innate memory (IM) CD8(+) T cells is now well-established in mice, whether an equivalent memory NK-like T-cell population exists in humans remains under debate. We recently reported that CD8(+) T cells responding to innate-like IL-12+IL-18 stimulation and co-expressing the transcription factor Eomesodermin (Eomes) and KIR/NKG2A membrane receptors with a memory/EMRA phenotype may represent a new, functionally distinct innate T cell subset in humans. In this review, after a summary on the known innate CD8(+) T-cell features in the mouse, we propose Eomes together with KIR/NKG2A and CD49d as a signature to standardize the identification of this innate CD8(+) T-cell subset in humans. Next, we discuss IL-4 and IL-15 involvement in the generation of innate CD8(+) T cells and particularly its possible dependency on the promyelocytic leukaemia zinc-finger factor (PLZF) expressing iNKT cells, an innate T cell subset well-documented for its susceptibility to tumor immune subversion. After that, focusing on cancer diseases, we provide new insights into the potential role of these innate CD8(+) T cells in a physiopathological context in humans. Based on empirical data obtained in cases of chronic myeloid leukemia, a myeloproliferative syndrome controlled by the immune system, and in solid tumors, we observe both the possible contribution of innate CD8(+) T cells to cancer disease control and their susceptibility to tumor immune subversion. Finally, we note that during tumor progression, innate CD8(+) T lymphocytes could be controlled by immune checkpoints. This study significantly contributes to understanding of the role of NK-like CD8(+) T cells and raises the question of the possible involvement of an iNKT/innate CD8(+) T cell axis in cancer.